Revitalization of Mosque Funds Management for Economic Empowerment - ULLYA NINDYANINGTYAS, 091614553021 (Science and Technology Publications, Lda, 2018)
This study aims to determine the development of the role of the mosque, especially the development of mosque fund management and offers revitalization of mosque fund management in the modern era. This research uses qualitative approach with literature study method. The results of the research analysis show that the potential ability of the Moslem community to restore the function of the mosque as in the time of the Prophet who not only used the mosque to facilitate his affairs in worship (mahdhah), but also as the center of Moslem activities in various fields (ghairu mahdhah) the provision of facilities and utilize mosque funds for the empowerment of people with modern mosque fund management system, so that the mosque becomes independent which can also create various programs that attract the public and the community to play an active role.